Commentary on the 1969 Vienna Convention on the Law of Treaties - Villiger, Mark Eugen (Martinus Nijhoff Publishers, 2009)
The 1969 Vienna Convention on the Law of Treaties, regulating treaties between States, lies at the heart of international law. This commentary interprets the Convention's 85 articles clearly and precisely. It covers such major topics as reservations to treaties, their interpretation and the grounds for terminating a treaty, for instance breach. This commentary is a must for practitioners and academics wishing to establish the meaning and scope of the provisions of the Vienna Convention on the Law of Treaties.